Interactions between Parabacteroides goldsteinii CCUG 48944 and diet ameliorate colitis in mice via regulating gut bile acid metabolism - Fujian Qin; Mengdi Zhang; Qingling Yang; Lei Wu; Tianxiao Mao; Xingchen Zhou; Jing Li; Maode Lai (iMetaOmics)
Abstract Inflammatory bowel disease (IBD) is a chronic disorder linked to an increased risk of colorectal cancer (CRC) and is characterized by significant dysbiosis in the gut microbiota. The commensal bacterium Parabacteroides goldsteinii (P. goldsteinii) has shown potential in modulating host metabolism and inflammatory responses. In this study, we investigated the probiotic properties of P. goldsteinii and its mechanism of action in IBD models, with a particular focus on bile acid metabolism and diet‐microbiota interactions. Fecal samples from patients with ulcerative colitis (n = 14), Crohn's disease (n = 22), and healthy controls (n = 13) were analyzed to assess P. goldsteinii relative abundance. In dextran sulfate sodium (DSS)‐induced colitis and azoxymethane (AOM)/DSS‐induced CRC mouse models, administration of P. goldsteinii significantly attenuated inflammation and tumorigenesis, particularly under fiber‐free diet conditions. Metabolomic profiling revealed an enrichment of secondary bile acids in P. goldsteinii‐treated mice, suggesting a link between bile acid metabolism and its anti‐inflammatory effects. Further mechanistic studies using bile salt hydrolase inhibitors and Tgr5 knockout mice confirmed the role of bile acid regulation in mediating the therapeutic benefits of P. goldsteinii. Additionally, we found that dietary factors significantly influenced the colonization and metabolic activity of P. goldsteinii, thereby modulating its probiotic efficacy. This highlights the potential for microbiome‐based therapies tailored to specific dietary contexts in the treatment of IBD. Our findings demonstrate that P. goldsteinii can modulate gut bile acid metabolism to alleviate colitis, making it a promising candidate for probiotic applications in IBD management, with dietary modulation enhancing its therapeutic potential.